New writing in Japan (Penguin, 1972)
First published by Penguin Books in 1972, the reissue of this volume is long overdue. The book contains 37 examples of poetry and short stories by 18 acclaimed writers, including Oe Kenzaburo, Abe Kobo, Ishihara Shintaro and Mishima himself.